Analisa Kinerja Keuangan Pada Pt. Astra International Tbk Periode 2012-2017 Dari Sudut Pandang Analisis Rasio Keuangan Dan Metode Du Pont - Roben Wijaya (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This study aims  to analyze and measure financial performance of PT. Astra International Tbk. using financial ratio analysis and du pont analysis. In conducting the research, data taken from company financial statement from 2012 until 2017. From financial ratio analysis, in liquidity ratio, capital structure ratio, asset management efficiency ratio, profitability ratio and market value ratio indicated if the company has increased every year. From du pont analysis show a continuous increase in Net Profit Margin and Total Asset Turnover every year. This increase is a positive increase so that the financial performance of PT. Astra International in the 2012-2017 period had declined but began to improve starting in 2016 because starting in 2016, the company could manage assets well and efficiently.